2014
DOI: 10.1155/2014/657512
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic Actions of Methyl Gallate on Neonatal Rat Cardiac Myocytes Exposed to H2O2

Abstract: Reactive oxygen species trigger cardiomyocyte cell death via increased oxidative stress and have been implicated in the pathogenesis of cardiovascular diseases. The prevention of cardiomyocyte apoptosis is a putative therapeutic target in cardioprotection. Polyphenol intake has been associated with reduced incidences of cardiovascular disease and better overall health. Polyphenols like epigallocatechin gallate (EGCG) can reduce apoptosis of cardiomyocytes, resulting in better health outcomes in animal models o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…Thus, kinases are not essential for TF3-mediated cardioprotection [70]. In the same cell model and again in comparison to EGCG, methyl gallate, a methyl ester of gallic acid, inhibits apoptosis by decreasing intracellular ROS generation, increasing reduced glutathione levels and maintaining mitochondrial membrane potential [71].…”
Section: Flavanolsmentioning
confidence: 96%
“…Thus, kinases are not essential for TF3-mediated cardioprotection [70]. In the same cell model and again in comparison to EGCG, methyl gallate, a methyl ester of gallic acid, inhibits apoptosis by decreasing intracellular ROS generation, increasing reduced glutathione levels and maintaining mitochondrial membrane potential [71].…”
Section: Flavanolsmentioning
confidence: 96%
“…Methyl gallate exhibits a better cardio‐protective effect in comparison to gallic acid as observed in neonatal rat cardiomyocytes challenged with hydrogen peroxide, and improves the mitochondrial functions and increases GSH synthesis . EGCG protects the cardiomyocytes against fluoride‐induced toxicity by improving the functions of several mitochondrial enzymes involved in respiration and metabolism, consequently downregulating the oxidative stress‐induced apoptosis .…”
Section: Cardio‐protective Effects Of Gallatesmentioning
confidence: 99%
“…The results showed that 8 did not demonstrate cytotoxic effects. Khurana et al [77] observed that 8 was able to preserve the viability of neonatal rat cardiomyocytes exposed to H 2 O 2 by decreasing intracellular ROS, maintaining mitochondrial membrane potential, augmenting endogenous glutathione, and reducing apoptosis. Whang et al [75] described that 8 was able to protect HUVEC from oxidative stress.…”
Section: Isolated Compounds From Brazilian Medicinal Plants With Diurmentioning
confidence: 99%